2011
DOI: 10.2478/s11533-011-0059-2
|View full text |Cite
|
Sign up to set email alerts
|

A solution of an open problem concerning Lagrangian mean-type mappings

Abstract: The problem of invariance of the geometric mean in the class of Lagrangian means was considered in [Głazowska D., Matkowski J., An invariance of geometric mean with respect to Lagrangian means, J. Math. Anal. Appl., 2007, 331(2), 1187–1199], where some necessary conditions for the generators of Lagrangian means have been established. The question if all necessary conditions are also sufficient remained open. In this paper we solve this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…For this reason it was hard to decide if the geometric mean G is, in fact, invariant with respect to the pair L f , L g . This problem remained unsolved until 2011 when G lazowska [68] showed that this is not the case. This was done by calculating partial derivatives of order 7 of L f and L g satisfying (5.5).…”
Section: Lagrangian Meansmentioning
confidence: 99%
“…For this reason it was hard to decide if the geometric mean G is, in fact, invariant with respect to the pair L f , L g . This problem remained unsolved until 2011 when G lazowska [68] showed that this is not the case. This was done by calculating partial derivatives of order 7 of L f and L g satisfying (5.5).…”
Section: Lagrangian Meansmentioning
confidence: 99%
“…J. M. Borwein and P. B. Borwein [9] extended some earlier ideas [19,32,63] and generalized this iteration to a vector of continuous, strict means of an arbitrary length. For several recent results about Gaussian product of means see the papers by Baják and Páles [4,5,6,7], by Daróczy and Páles [13,17,18], by Głazowska [21,22], by Matkowski [39,40,41,42], and by Matkowski and Páles [43]. Given N ∈ N and a vector (M 1 , .…”
Section: Means and Their Basic Propertiesmentioning
confidence: 99%
“…Inviant means in a family of quasi-arithmetic means were studied by many authors, for example Burai [7], Daróczy-Páles [11], J. Jarczyk [18], J. Jarczyk and Matkowski [20]. In fact invariant means were extensively studied during recent years, see for example the papers by Baják-Páles [1,2,3,4], by Daróczy-Páles [10,12,13], by Głazowska [15,16], by Matkowski [23,24,25], by Matkowski-Páles [27], by Pasteczka [29,32,30] and Matkowski-Pasteczka [26]. For details we refer the reader to the recent paper of J. Jarczyk and W. Jarczyk [19].…”
Section: Introductionmentioning
confidence: 99%